2007
DOI: 10.1038/sj.bjc.6603719
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review, including meta-analyses, on the management of locally advanced pancreatic cancer using radiation/combined modality therapy

Abstract: There is no consensus on the management of locally advanced pancreatic cancer, with either chemotherapy or combined modality approaches being employed (Maheshwari and Moser, 2005). No published meta-analysis (Fung et al, 2003;Banu et al, 2005;Liang, 2005;Bria et al, 2006;Milella et al, 2006) has included randomised controlled trials employing radiation therapy. The aim of this systematic review was to compare the following: (i) chemoradiation followed by chemotherapy (combined modality therapy) vs best support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(118 citation statements)
references
References 38 publications
(49 reference statements)
2
114
0
2
Order By: Relevance
“…In one study, while the median survival in patients who received only RT was 6 months, the survival in patients who underwent RT with 5FU chemotherapy increased to 10 months (Herreros-Villanueva et al, 2012). Sultana et al (2007) in their systematic review, which included a meta-analysis, showed that in locally advanced pancreatic cancer, CRT and survival increased only when compared with RT, and the risk of death was reduced by 32%. In this study, in patients who were operable and treated with CRT, the median survival was 12.5 months, while the 2-year survival was 34.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, while the median survival in patients who received only RT was 6 months, the survival in patients who underwent RT with 5FU chemotherapy increased to 10 months (Herreros-Villanueva et al, 2012). Sultana et al (2007) in their systematic review, which included a meta-analysis, showed that in locally advanced pancreatic cancer, CRT and survival increased only when compared with RT, and the risk of death was reduced by 32%. In this study, in patients who were operable and treated with CRT, the median survival was 12.5 months, while the 2-year survival was 34.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of gemcitabine with capecitabine was chosen as this could potentiate the vaccine effects and was also associated with significantly improved objective responses compared to gemcitabine alone. 22,37,38 Interpretation This is one of the largest randomized clinical trials ever undertaken in pancreatic cancer and the largest trial of vaccine therapy ever undertaken in any solid cancer type. There was no survival benefit from the addition of the GV1001 vaccine to gemcitabine and capecitabine in patients with advanced pancreatic cancer.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Previous randomized trials had shown that radiochemotherapy was superior to radiotherapy alone in treatment of locally advanced patients [5,6] . The treatment for patients with systemically advanced disease remains palliative and these 111111 patients should be offered an opportunity to take new available treatments [7] .…”
Section: Introductionmentioning
confidence: 99%